Pre-schoolers' transport imaginaries: Moving towards sustainable futures?. (April 2020) - Ergler, Christina R.; Freeman, Claire; Guiney, Tess
Abstract: Being on the move is part of children's everyday life in cities. However, little is known about how young children experience transport systems or their aspirations for mobility in cities. In this paper, we explore pre-schoolers' experiences with the mobile world and show their affinity with different transport modes and hopes for their current transport system. We draw on a participatory research project that engaged children in class discussions, a tile-based city building exercise and neighbourhood walks. Findings suggest that although the voices of children aged 3–5 years are absent in mobility or transport debates, children are fascinated by mobility and transport related activities and services. Pre-schoolers from Dunedin, New Zealand, though recognising a predominantly motorised transport system, also showed creative or alternative modes making their way into their own transport systems. In this paper we argue that children should be introduced to and experience alternative modes of transport in the early years to allow for more imaginary transport geographies creating greater support for more sustainable, liveable urban environments for all ages. Highlights: Young children's current urban experiences shape their view on transport. Children replicated and regurgitated the domination of the automobility system. Children need to experiment with alternative modes of transport. Doing/being/thinking sustainable transport systems starts from birth. Need to expand children's imaginary horizon for moving to sustainable transport.